PENGARUH MUTU TABUNGAN DAN PROMOSI PENJUALAN TERHADAP MINAT MENABUNG NASABAH PADA PT. BANK SULSELBAR MAKASSAR - Mohammad Ali Wairooy (Movere Journal, 2021)
This study aims to examine and analyze the effect of quality of savings on customer saving interest at PT. Bank SULSELBAR Makassar, To test and analyze the effect of Sales Promotion on Customer Saving Interest at PT. Bank SULSELBAR Makassar, and to test and analyze the effect of the Quality of Savings and Sales Promotion simultaneously on Customers' Interest in Saving at PT. Bank SULSELBAR Makassar. Data collection using primary data obtained from a questionnaire with a population of 165,957 customers and samples using the Slovin formula obtained as many as 100 respondents. The results of the questionnaire have been tested for validity and reliability, as well as tested classical assumptions in the form of normality assumptions and heteroscedasticity assumptions. Methods of data analysis using multiple regression techniques. Based on the partial analysis (t-test) and simultaneously (Test-f) it turns out that the research results prove that all hypotheses are accepted because the Quality of Savings and Sales Promotion has a positive and significant effect partially and simultaneously on Saving Interest at PT. Bank SULSELBAR Makassar.